The institutional dynamics of inequality for women inventors who break with conventional thinking - Tara Sowrirajan; Ryan Whalen; Brian Uzzi (Proceedings of the National Academy of Sciences, 2026)
Though women comprise a growing share of the scientific workforce, the gender innovation gap in patenting between men and women inventors persists, potentially limiting innovation output and equity. We study millions of scientific and technological innovations and find that the innovation gap faced by women is not universal. No gap exists for highly conventional innovations, which combine ideas in familiar ways. Rather, it exists when women inventors attempt to patent unconventional inventions, which combine ideas in surprising ways and drive scientific advancements. Our data suggest that rather than deliberate bias, a confluence of institutional practices lower women inventor’s chances of patenting unconventional innovations. We find that women examiners relative to men have less of the on-the-job experience needed to appraise unconventional innovations. Additionally, women examiners are overassigned to women applicants, reducing their odds of successfully patenting unconventional inventions. Lastly, traditional explanations weakly account for this innovation gap because men examiners grant comparably more unconventional innovations to women inventors than do women examiners. These institutional barriers reveal new factors that slow innovation, but at the same time can be more directly addressed than deeply rooted gender norms.